COMPARISON OF THE EFFECT OF CURRENT RATIO (CR) AND DEBT TO EQUITY RATIO (DER) ON RETURN ON ASSETS (ROA) IN RETAIL TRADE AND TELECOMMUNICATION SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) - Chaerudin, Abdul Rauf; Abdurrasyad, Rayhan (LPPM Universitas Bina Bangsa, 2025)
Company performance is an important indicator to assess how well a company has achieved its goals. Financial performance can be shown through financial reports, one way to determine company performance is by using the profitability ratio. This study aims to determine the comparative effect of Current Ratio and Debt to Equity Ratio on Return On Assets in retail trade and telecommunications sub-sector companies listed on the Indonesia Stock Exchange. The method in this study is to use a quantitative research approach, where the population in this study for retail trade sub-sector companies is 6 samples from 39 companies, while for telecommunications sub-sector companies is 4 samples from 23 companies. The sampling technique in this study is purposive sampling. The data analysis technique in this study uses the classical assumption test and multiple linear regression analysis using IBM SPSS version 26. Then the results are compared between companies in the retail trade and telecommunications sub-sectors listed on the Indonesia Stock Exchange. Comparison of the results in this study shows that in the retail trade sub-sector companies listed on the Indonesia Stock Exchange partially Current Ratio has a positive and significant effect on Return On Assets, and Debt to Equity Ratio has a negative and insignificant effect on Return On Assets, simultaneously or together there is an influence and significant between the variables Current Ratio and Debt to Equity Ratio on Return On Assets. While in the telecommunications sub-sector companies listed on the Indonesia Stock Exchange partially Current Ratio has a positive and significant effect on Return on Assets, and Debt to Equity Ratio has no effect and is not significant on Return on Assets, simultaneously Current Ratio and Debt to Equity Ratio together have a positive and significant effect on Return on Assets.